Symmetry-Related Electromagnetic Properties of Resonator-Loaded Transmission Lines and Applications - Jordi Naqui; Lijuan Su; Javier Mata; Ferran Martín (Applied Sciences, 2015)
This paper reviews the recent progress in the analysis and applications of the symmetry-related electromagnetic properties of transmission lines loaded with symmetric configurations of resonant elements. It will be shown that the transmission characteristics of these reactively loaded lines can be controlled by the relative orientation between the line and the resonant elements. Two main types of loaded lines are considered: (i) resonance-based structures; and (ii) frequency-splitting structures. In resonance-based transmission lines, a line is loaded with a single resonant (and symmetric) element. For a perfectly symmetric structure, the line is transparent if the line and resonator exhibit symmetry planes of different electromagnetic nature (electric or magnetic wall), whereas the line exhibits a notch (resonance) in the transmission coefficient if the symmetry planes behave as either electric or magnetic walls (symmetric configuration), or if symmetry is broken. In frequency-splitting lines, paired resonators are typically loaded to the transmission line; the structure exhibits a single notch for the symmetric configuration, whereas generally two split notches appear when symmetry is disrupted. Applications of these structures include microwave sensors (e.g., contactless sensors of spatial variables), selective mode suppressors (of application in common-mode suppressed differential lines, for instance) and spectral signature barcodes, among others.